Administration of finerenone in chronic kidney disease - Mohsen Akhavan Sepahi; Elham Emami; Akshaya Ann Joseph; Shakiba Hassanzadeh; Mohammad Reza Razavi (Society of Diabetic Nephropathy Prevention, 2023)
Spironolactone is a first-generation and non-selective mineralocorticoid receptor antagonist (MRA). It is extensively well-studied and recommended due to increased accessibility for patients. Unfortunately, it is often discontinued in several cases due to its association with hyperkalemia. The apparent benefit of eplerenone over spironolactone is its mineralocorticoid receptor (MR) selectivity. However, it is also characterized by low-potency and higher cost compared to spironolactone. The high adverse-effect profile of spironolactone and eplerenone has led to the innovation of novel medications such as non-steroidal MRAs. Among these medications, finerenone is the most advanced agent. Finerenone is associated with decreased proteinuria, reduced risk of hyperkalemia and increased preservation of renal function with comparable benefit in heart failure compared to selective and nonselective MRAs. The nonsteroidal structure of finerenone affects mineralocorticoid receptor binding, lipophilicity and polarity which have potent effects on distribution, the degree of attachment to blood proteins, transportation, and tissue diffusion.